Słowa i ciało w Słońcu i stali Yukio Mishimy - Rojek, Ernest (Przestrzenie Teorii, 2025)
Ernest Rojek’s work The Word and The Body in Yukio Mishima’s ‘Sun and Steel’ aims is to provide an original interpretation of this text, taking the titular opposition as its starting point. These assumptions allow the coherent structure of this Japanese author’s essay to be presented, and his unique philosophical anthropology. The author of the paper makes use of the tools provided by Mieletinski’s semiotic theory of the myth and autotheory. Additionally, by providing the historical context, he draws attention to the Japanese and European influences of Mishima. He also shows that Mishima was a thinker with a profound conviction about the inner conflict in human existence, which lay between the bodily, and the linguistic reality. Inspired by Bataille and Neo-Confucian philosophy, Mishima was able to overcome this divide. In doing so, he creates his own original ars moriendi, in which death becomes the moment of return to the full being.